THE EFFECT OF USING PhET MEDIA ON UNDERSTANDING THE CONCEPT OF STRAIGHT MOTION OF HIGH SCHOOL STUDENTS - Sri Astuti; Linda Febriana (Jurnal Inovasi Fisika dan Edukasi, 2025)
This study aims to analyze the effect of using PhET interactive simulation media on understanding the concept of straight motion of high school students. The background of this study is based on the low understanding of students of the basic concepts of physics that are abstract, especially in the topic of straight motion. The research method used is quantitative with a quasi-experimental design using the Nonequivalent Control Group Design model. The research subjects consisted of 60 grade X students who were divided into two groups, namely the experimental group using PhET media and the control group using conventional learning methods. The main instrument used was a concept understanding test in the form of validated multiple choice. Data were analyzed using N-Gain test and independent sample t-test. The results showed that the increase in concept understanding in the experimental group was in the high category with an average N-Gain of 0.72, while the control group only reached the medium category with an average N-Gain of 0.47. The t-test showed a significance value of 0.000 (p < 0.05) indicating that there was a significant difference between the two groups. This finding shows that the use of PhET media can significantly improve students' understanding of the concept of straight motion. Interactive simulations in PhET provide visual and contextual learning experiences that support students' knowledge construction of the concept of motion. This study recommends the use of PhET media as an alternative in physics learning to improve the quality of students' concept understanding, and opens up opportunities for the development of similar media on other physics materials.